Komparasi Implementasi Partisipasi Perempuan dan Sistem Pemilu di Negara Indonesia dan Australia - Zuniati, Annisa Risky; Maulidza, Raisha; Sabilla, Najwa; Ummah, Anniqotul (Jurnal Ilmu Politik dan Pemerintahan, 2024)
Women's political participation and the electoral system are two key factors in strengthening democracy in each country. This study aims to investigate the extent to which political, cultural and structural factors influence women's political participation in the two countries. The presence of women in representative numbers in parliament will not only have an impact on political decisions relating to gender equality and justice, but will also be an indicator of improving the quality of democracy. The method applied in this research is a qualitative approach with literature study data collection techniques. The results of this study are that Indonesia and Australia still need serious attention to women's political representation. In Indonesia, although there are regulations that set quotas for women's representation in general elections, implementation is still not optimal, with a significant gap between targets and realization. Australia has made progress in women's representation in parliament, but there are still imbalances that need attention. Challenges include gender stereotypes, lack of support from political parties, and social issues such as "toxic masculinity" that affect perceptions of women's roles in politics.